ERP-Based Warehouse System Implementation Using Odoo for Steel Fabrication Stock Accuracy: Penerapan Sistem Gudang Berbasis ERP Menggunakan Odoo untuk Menjamin Akurasi Persediaan dalam Industri Fabrikasi Baja - Rochman, Mohammad Habibur; Ernawati, Dira; Nugraha, Isna (Universitas Muhammadiyah Sidoarjo, 2026)
This study presents an integrated approach to warehouse management in the steel fabrication sector. General Background: Manufacturing industries rely on efficient supply chain and warehouse operations to maintain competitiveness and ensure accurate material flow. Specific Background: Steel fabrication companies experience material management issues due to semi-manual and non-integrated systems, resulting in significant stock discrepancies reaching 12% of total inventory. Knowledge Gap: Prior studies on ERP and Warehouse Management Systems remain general and lack specific implementation insights using Odoo in steel fabrication environments with complex material structures. Aims: This study aims to design and implement an ERP-based Warehouse Management System using Odoo to address stock inaccuracies and operational inefficiencies. Results: The implementation of integrated modules, including Inventory, Purchase, and Manufacturing, combined with Black Box Testing, reduces stock discrepancies, improves data accuracy, enables real-time monitoring, and strengthens coordination across procurement, warehouse, and production divisions. Novelty: This study provides a practical implementation of an Odoo-based ERP-WMS tailored to steel fabrication conditions characterized by high inventory complexity and integration needs. Implications: The system supports structured production planning, improves operational performance, and facilitates data-driven decision-making in warehouse and supply chain management. Highlights: Integrated modules streamline coordination among procurement, storage, and production units. Real-time monitoring capability minimizes discrepancies between recorded and actual inventory. System testing confirms alignment with operational requirements and functional needs. Keywords: Warehouse Management System, Enterprise Resource Planning, Odoo, Material Procurement, Steel Fabrication